Pseudo-Foster Kennedy Syndrome Secondary to Multiple Sclerosis with Hypertensive and Ischemic Overlap: A Rare Neuro-ophthalmic Presentation - Sharmila, Shaik; Yanamadala, Pavan Kumar; Gope, Janani; Jammula, Damini Sai Kumar; Mandarapu, Bhargavi Devi; Nadendla, Rama Rao (Indian Journal of Pharmacy Practice)
Background: Pseudo-Foster Kennedy Syndrome (PFKS) represents an uncommon neuro-ophthalmic condition distinguished by the presence of ipsilateral optic atrophy alongside contralateral papilledema, occurring in the absence of an intracranial mass. This syndrome is generally attributed to a series of injuries to the optic nerve resulting from ischemic or demyelinating events. Case Presentation: A 39-year-old male patient exhibited a gradual decline in vision accompanied by headaches. Upon examination of the fundus, right optic atrophy and left disc oedema were observed. MRI scans of the brain and spine revealed numerous periventricular and juxtacortical plaques indicative of Multiple Sclerosis (MS), in addition to acute ischemic infarcts. Notably, severe hypertension was recorded at the time of presentation. Analysis of cerebrospinal fluid indicated a slight increase in protein levels without any mass effect. The interplay of chronic demyelinating optic neuropathy, a hypertensive crisis, and acute ischemic damage resulted in a clinical picture resembling that of PFKS. Management and Outcome: The patient received treatment involving intravenous antihypertensives, antiplatelet therapy, statins, and immunomodulation using interferon-β. The papilledema resolved following the management of blood pressure; however, optic atrophy remained. Conclusion: This seems to be the initial recorded instance of PFKS in India, resulting from a combination of multiple sclerosis, hypertensive crisis, and ischemic stroke. It emphasises the significance of linking fundus observations with neuroimaging to differentiate PFKS from tumour-associated FKS and stresses the necessity of acknowledging multisystem vascular-inflammatory interactions to avert permanent visual consequences.
Keywords: Pseudo-Foster Kennedy Syndrome; Multiple Sclerosis; Optic Atrophy; Papilledema; Hypertensive Encephalopathy; Ischemic Optic Neuropathy; Neuro-ophthalmology